Problematika Penghimpunan Dana Zakat di LAZNAS Baitul Maal Hidayatullah Perwakilan Bengkulu - Syafrizal Syafrizal; Herlina Yustati (FEB Universitas Sultan Ageng Tirtayasa, 2019)
The purpose of this study was to analyze the problematic collection of Zakat Funds in LAZNAS Baitul Maal Hidayatullah Bengkulu Representative, covering collection strategies, constraints, and ways to overcome the constrainst of raising zakat funds. To uncover the problem in depth and thoroughly, the researcher uses a qualitative method, directly to the field to see the phenomena that occur. The results showed the collection of zakat funds at LAZNAZ Baitul Maal Hidayatullah Bengkulu Representative has 2 (two) strategies: first internal strategy and second external strategy. The problem of collecting zakat funds in LAZNAS Baitul Maal Hidayatullah Bengkulu Representative namely, the lack of human resources and the lack of funds to socialized in collecting zakat funds. To overcome these problems LAZNAZ Baitul Maal Hidayatullah Bengkulu Representative facilitated and attended training or workshops to broaden employee insights, as well as working with preachers to socialize LAZNAS Baitul Maal Hidayatullah Bengkulu Representative.